Plasmaspheric filament: an isolated magnetic flux tube filled with dense plasmas. Issue 2 (30th January 2013) - Murakami, Go; Yoshikawa, Ichiro; Yoshioka, Kazuo; Yamazaki, Atsushi; Kagitani, Masato; Taguchi, Makoto; Kikuchi, Masayuki; Kameda, Shingo; Nakamura, Masato
Abstract [1] The Telescope of Extreme Ultraviolet (TEX) onboard Japan's lunar orbiter KAGUYA provided the first sequential images of the Earth's plasmasphere from the "side" (meridian) view. The TEX instrument obtained the global distribution of the terrestrial helium ions (He+) by detecting resonantly scattered emission at 30.4 nm. One of the most striking features of the plasmasphere found by TEX is an arc‐shaped structure of enhanced brightness, which we call a "plasmaspheric filament". In the TEX image on 2 June 2008, the filament structure was clearly aligned to the dipole magnetic field line of L = 3.7 at 7.3 magnetic local time. Our analysis suggests that the filament represents an isolated flux tube filled with four times higher He+ density than its neighbors. We found four events of plasmaspheric filament in the images obtained between March and June 2008, and in all four events, the geomagnetic activity was quite low. The plasmaspheric filament in the TEX image is the first evidence that a "finger" structure seen in the IMAGE‐EUV image is the projection of an isolated flux tube.